(untitled) (Balneo and PRM Research Journal, 2022)
Abstract: (1) Background: Aortic stenosis is the most common valvulopathy in elderly patients over 60 years of age. The absence of immediate surgical intervention through classic valve replacement or through a minimally invasive procedure, namely transcatheter implantation of the aortic valve (TAVI) leads to an increase in the risk of morbidity and mortality through the deterioration of the clinical condition. Since the first interventional transcatheter aortic valve implantation procedure was performed in 2012 and until now, the progression of medical technology and state-of-the-art valves have led to the refinement of the treatment strategy and the improvement of the prognosis of patients with aortic stenosis undergoing TAVI in the first 6 months after the procedure; (2) Methods: We conducted a prospective study in which 86 patients diagnosed with severe aortic stenosis underwent minimally invasive valve replacement by TAVI; (3) Results: The presence of preoperative anemia is associated with a negative prognosis both in the medium term and in evolution, and in addition to hematological parameters, we also evaluated a series of biochemical data, with special attention to renal function and lipid profile; (4) Conclusions: Biological parameters followed after TAVI may be predictors associated with a negative long-term prognosis.